Prednisone for the Treatment of Acute Nonspecific Mesenteric Lymphadenitis - Pavlovic, Momcilo; Rokvic, Zeljko; Berenji, Karolina (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Acute nonspecific mesenteric lymphadenitis refers to a common pediatric problem that has no specific treatment. CASE REPORT: In our study, we describe seven children presenting with abdominal pain as the main symptom of a disease. All patients were treated with prednisone 1 mg/kg (max 40 mg daily) for a maximum of 5 days. In addition, we evaluated the intensity of the pain using a numeric rating scale and achieved a clinically important difference in acute pain relief of 85.3%. After administering corticosteroid therapy, the abdominal pain resolved after 1.7 (1–4) days in all children without any other disturbances. CONCLUSION: In selective patients with mesenteric lymphadenitis, prednisone can be used as an acceptable form of treatment to reduce the duration of abdominal pain.